NEW AND CRITICAL MALAYSIAN PLANTS-II* - A. J. G. H. KOSTERMANS (REINWARDTIA, 1954)
In the present paper 14 new species of Pithecellobium Mart, are described and 3 new combinations are made with that name.Notes on several species of the related genus Archidendron F. Muell, are added.